Axonal regulation of dopamine transmission by striatal neuromodulators - Cragg, Stephanie J.; Sulzer, David; Todd, Kathryn (Handbook of Behavioral Neuroscience, 2025)
Striatal dopamine release can be modulated by diverse neuromodulators acting throughout the full anatomical extent of dopamine neurons, from dendrites and soma in the midbrain to axons in the striatum. Besides influencing somatodendritic integration and generation of action potentials by dopamine neurons, neuromodulators act on axons to shape axonal excitability and neurotransmitter release probability. Mesostriatal dopamine axons are immensely arborized, forming thousands of branches per neuron and 105 potential release sites per axonal tree, comprising more than 99% of the surface of the neuron. Dopamine axons therefore offer strategic sites for the regulation of dopamine output by striatal neuromodulators that will then shape dopamine function and dysfunction, and potentially offer therapeutic opportunities for treating dopaminergic disorders. Here, we summarize current knowledge of the striatal neuromodulators and corresponding receptors that influence dopamine release and their underlying circuits where known.